Hepatocellular carcinoma with main portal vein tumor thrombus: a comparative study comparing hepatectomy with or without neoadjuvant radiotherapy. Issue 6 (June 2016) - Li, Nan; Feng, Shuang; Xue, Jie; Wei, Xu-Biao; Shi, Jie; Guo, Wei-Xing; Lau, Wan-Yee; Wu, Meng-Chao; Cheng, Shu-Qun; Meng, Yan
Abstract: Background: Hepatocellular carcinoma (HCC) with main portal vein tumor thrombus (mPVTT) has a poor prognosis even after surgical resection. Whether neoadjuvant radiotherapy improves surgical outcomes is currently unknown. The aim of this study was to compare the survival of patients with resectable HCC and mPVTT who underwent neoadjuvant therapy to those who underwent surgery alone. Methods: A non-randomized comparative study was performed. For patients in the neoadjuvant radiotherapy group, three-dimensional conformal radiotherapy was administrated with a daily fraction of 300 cGy in 6 consecutive days. Hepatectomy was carried out 4 weeks after completion of irradiation. Results: 95 patients were enrolled into this study. In the neoadjuvant radiotherapy group (n = 45), 12 patients showed gross radiological reduction in extent of PVTT. In 6 patients, the extent of PVTT was reduced to be within the ipsilateral side of the portal vein. When compared with patients who underwent surgery alone (n = 50), neoadjuvant radiotherapy significantly decreased the rates of HCC recurrence and HCC-related death, with hazard ratios of 0.36 (95% CI, 0.19–0.70) and 0.32 (95% CI, 0.18–0.57), respectively. Conclusion: For patients with HCC with mPVTT, neoadjuvant radiotherapy before partial hepatectomy provided better postoperative survival outcomes than partial hepatectomy alone.